Relationship between depressive symptoms and stigma with the need and willingness to receive counseling services among public university students in Sarawak - Habib, Muhammad Abdul Rahim; Zakaria, Noor Syamilah; Md Joni, Amirul Azuan; Wan Othman, Wan Norhayati; Adenan, Faizul (Human Resource Management Academic Research Society, 2022)
This study aimed to identify the relationship between depressive symptoms and stigma with the need and willingness to seek counselling services. Pearson’s correlation, t-test and ANOVA was applied in this study to obtain the direction and strength of the relationship that exists between the variables. A total of 348 university students aged 18 to 26 years and above were involved in this study which was conducted at a public university in Sarawak. The findings of the study indicate that there is a positive correlation between the variables of depressive symptoms and stigma with readiness and the need to seek counselling. While there is a difference in depressive symptoms reported higher among the group who had sought counselling compared to the group who had never sought counselling. Even so, the group that never sought counselling was reported to have higher differences from stigma and the need and willingness to seek counselling. ANOVA analysis showed that there was no significant difference between the Cumulative Grade Point Average (CGPA) among students in public universities on depressive symptoms. The main implications of this study lead to the improvement of counselling services in universities to improve the existing counselling system and management.